Pengaruh model project-based learning berbantuan geogebra terhadap hasil belajar matematika materi bangun ruang sisi datar di madrasah ibtidaiyah - Tilari, Aji Ginti; Firmansyah, Fadli Anwar; Cipta, Eliva Sukma (IKIP Siliwangi, 2024)
The purpose of this study was to determine whether there is a difference in the average increase in student learning outcomes at the elementary level using Geogebra-assisted project-based learning (PjBL) compared to the Conventional learning model. This research is a pseudo-experimental research with a quantitative approach. The model used is the nonequivalent control group model. The population of this study were all students of Class V MI I'anatut Thalibin and Class V SDN Cangkuang 08. In this study using purposive sampling technique. The instruments used were tests consisting of pre-test and post-test. N-Gain was used to determine the increase in student scores before and after the test. The results of the Independent t test show that there is a difference in the improvement of learning outcomes between students who learn using the Geogebra-assisted PjBL model and students who learn using the conventional model. Furthermore, based on the average N-Gain, the PjBL-assisted Geogebra class is greater than the conventional class. The results of the N-Gain calculation show that the application of the Geogebra-assisted PjBL learning model can improve student learning outcomes.